Analysis of Intrinsic Element Found in It Ends With Us by Colleen Hoover - Zuhroni, Zuhroni; Syamsurrijal, Syamsurrijal (Jurnal Ilmu Sosial dan Humaniora, 2023)
In research of literature will be better if combined with intrinsic elements that can attract the interest of readers. Analysis of this novel aims to describe the intrinsic elements contained in the novel It End With Us by Colleen Hoover. The data source used in this research is the novel It Ends With Us by Colleen Hoover. The researcher used method qualitative descriptive to analysis this novel. The result of this study indicate that the novel It Ends With Us by Colleen Hoover there is a theme that is a women who is trying to get out of a toxic relationship, a variety of character, using a back and forth plow, with the background place and time. The point of view that it used is the first person and there is a mandate to value a relationship and the mandate contained in the novel It Ends With Us by Colleen Hoover is to respect someone and should not judge someone by the mistake they have made.